KEARIFAN LOKAL UPACARA PERKAWINAN ADAT SUKU LINGGAU - Rosmaidar, Rosmaidar (Jurnal Ilmiah Bina Bahasa, 2020)
This study aimed to (1) describe the Linggau tribal marriage ceremony, and (2) analyze the local wisdom contained in the Linggau tribal marriage ceremony with a descriptive method based on a qualitative approach. The data source was a traditional marriage ceremony that developed among the Linggau tribe community. Data and information were collected from informants who know the ins and outs of the marriage ceremony of the Linggau tribe, Ona (75 years) who is a traditional figure who resides in the Batu Batu Urip Taba, Lubuk Linggau. Data collection was obtained from the results of listening and taking notes and recording. In addition, unstructured interviews were also used to further explore the traditional ceremonies of the Lubuk Linggau tribe. The method used in this research was the descriptive method.